2021
DOI: 10.5005/jp-journals-10005-1888
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of Marginal Accuracy of Co–Cr Metal Copings Fabricated Using Traditional Casting Techniques and Metal Laser Sintering

Abstract: A bstract Aims and objectives The aim and objective of the study were to determine the amount of marginal discrepancy produced by cobalt–chromium (Co–Cr) copings fabricated using two different fabrication methods, i.e., traditional casting and direct metal laser-sintering (DMLS), and compare the values obtained between each fabrication technique and to evaluate if the fabrication technique can produce prosthesis that is within the standards of clinical acceptance of marg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…Clinical experience with cast alloy RPDs has demonstrated that it is rare for a specific framework to suit the mouth perfectly without requiring some adjustments [9][10][11]. The intricacy of the work stages used in RPDs and the use of high-shrinkage alloys in the frameworks may be to blame for this misfit [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical experience with cast alloy RPDs has demonstrated that it is rare for a specific framework to suit the mouth perfectly without requiring some adjustments [9][10][11]. The intricacy of the work stages used in RPDs and the use of high-shrinkage alloys in the frameworks may be to blame for this misfit [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Rapid prototyping (RPr) techniques and other cutting-edge technology, such as computer-aided designing and manufacturing (CAD/CAM) techniques, have recently revolutionized the field of prosthodontics. These techniques are used extensively for both removable dentures and maxillofacial/craniofacial prostheses [9][10][11]. The level of fit in RPD frameworks is thought to be improved by the use of the RPr, which has also been used to create RPDs [14].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies evaluate axial and occlusal marginal values separately; in others, the evaluation was made without discrimination. 1,9,[12][13][14][15] Akçin et al reported that there was a decrease in marginal discrepancy in three-unit restorations in areas far from the body at metal substructures. 12 Kim et al also evaluated marginal discrepancy according to the production method and achieved similar results in restorations produced by DMLS.…”
Section: Discussionmentioning
confidence: 99%